Predictors of appropriate implantable cardiac defibrillator therapy in cardiac sarcoidosis. (15th April 2022) - Mathijssen, Harold; Bakker, Annelies L. M.; Balt, Jippe C.; Akdim, Fatima; van Es, H. Wouter; Veltkamp, Marcel; Grutters, Jan C.; Post, Marco C.
Abstract: Background: Cardiac sarcoidosis (CS) is associated with an increased risk for sudden cardiac death. An implantable cardiac defibrillator (ICD) is recommended in a subgroup of CS patients. However, the recommendations for primary prevention differ between guidelines. The purpose of the study was to evaluate the efficacy and safety of ICDs in CS and to identify predictors of appropriate therapy. Methods: A retrospective cohort study was performed in CS patients with an ICD implantation between 2010 and 2019. Primary outcome was appropriate ICD therapy. Independent predictors were calculated using Cox proportional hazard analysis. Results: 105 patients were included. An ICD was implanted for primary prevention in 79%. During a median follow‐up of 2.8 years, 34 patients (32.4%) received appropriate ICD therapy of whom 24 (22.9%) received an appropriate shock. Three patients (2.9%) received an inappropriate shock due to atrial fibrillation. Independent predictors of appropriate therapy included prior ventricular arrhythmias (hazard ratio [HR]: 10.5 [95% confidence interval (CI): 5.0–21.9]) and right ventricular late gadolinium enhancement (LGE) (HR: 3.6 [95% CI: 1.7–7.6]). Within the primary prevention group, right ventricular LGE (HR: 5.7 [95% CI: 1.6–20.7]) was the only independent predictor of appropriate therapy. Left ventricular ejection fraction did not differ between patients with and without appropriate therapy (44.4% vs. 45.6%, p = .70). Conclusion: In CS patients with an ICD, a high rate of appropriate therapy was observed and a low rate of inappropriate shocks. Prior ventricular arrhythmias and right ventricular LGE were independent predictors of appropriate therapy.